2008
DOI: 10.1007/s00276-008-0421-7
|View full text |Cite
|
Sign up to set email alerts
|

The terminal insertional segments and communications of the vertebral nerve in the human cervical region

Abstract: Twenty-four cadavers (48 sides) were used to clarify the terminal insertional segment and communications of the vertebral nerve in the cervical region under a surgical microscope. After displacing the prevertebral muscles (longus colli and longus capitis) laterally, the ventral parts of the transverse foramen of vertebrae (from C2 to C6) were removed, and the insertional segment and communicates of the vertebral nerve surrounding the vertebral artery were observed. The results showed: (1) the vertebral nerve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The vertebral artery and venous plexus are well protected within the transverse foramen periosteum [18]. The location of cervical sympathetic plexus is fairly distant from possible injury by the translaminar screw [24]. Based on these reports, the risk of iatrogenic neurovascular injury following translaminar screw insertion is minimal.…”
Section: Discussionmentioning
confidence: 79%
“…The vertebral artery and venous plexus are well protected within the transverse foramen periosteum [18]. The location of cervical sympathetic plexus is fairly distant from possible injury by the translaminar screw [24]. Based on these reports, the risk of iatrogenic neurovascular injury following translaminar screw insertion is minimal.…”
Section: Discussionmentioning
confidence: 79%
“…Hinoki found that over-excitation of the cervical sympathetic nerves and proprioceptors are related to the clinical entity of cervical vertigo 11) . Numerous sympathetic nerve endings on the surface of the vertebral artery control the flow of blood in the artery 6,7,15,16) . When the sympathetic nerve ending is stimulated abnormally, the vertebral artery may go into spasm, and this can cause posterior circulation ischemia and induce cervical vertigo 8,17) .…”
Section: 2) Discussionmentioning
confidence: 99%